Nigerian foreign policy under major-general Yakubu Gowon, 1966-1975 : factors and interests - Talibu, Oladimeji (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This study examines Nigeria's foreign policy under Major-General Yakubu Gowon. It analyses the internal and external factors that influenced Nigeria's foreign policy under Gowon. The research employs qualitative method of data collection. The historical overview of post-independent Nigerian foreign policy suggests that Nigeria's foreign policy under Gowon has been formulated in pursuit of national interests such as territorial integrity, citizen's welfare etc. The internal factors of Nigeria's foreign policy under Gowon identified in the study are: personality of Gowon, national interests, political terrain and economy. While external factors considered are: continental factor, major powers, the Cold War international system and the Middle East factor. This study found that Nigeria under Gowon began to assert independent foreign policy after it gained sovereignty from Britain in 1960. It also found that the Nigerian civil war that lasted for 3 years had a profound effect on Nigerian foreign policy under Gowon. The study recommends that Nigerian government should abandon its strategy of unwarranted financial aid that could be detrimental to the domestic economy. It also recommends that citizen's diplomacy is needed for dynamic foreign policy formulation.